2022
DOI: 10.1002/aff2.42
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of mud crab, Scylla olivacea (Herbst, 1796) from the Sundarbans of Bangladesh

Abstract: The Sundarbans mangrove regions are the home of the mud crab (Scylla olivacea) business, as forest areas are potential places for random crab harvesting, trading, and exporting overseas seafood markets. Since the mud crab was being captured on a large‐scale in the wild for various purposes, estimation of population parameters were immediately done in terms of body weight and length‐frequency data collected from different locations in the forest of southwestern Bangladesh to understand the status of the stock. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
2
6
3
Order By: Relevance
“…Although the b-value was less than 3 in numerous studies [5,19,22] of polychaetes conducted around the world, b reached 3.52 in Armandia maculata (Opheliidae), 4.27 in Bithynia tentaculata (Bithyniidae), and 2.36 in Naticidae mesogastropod species [29]. In addition, the mud crab (Scylla olivacea), found in Bangladesh's Sundarbans mangrove, has b-values of 3.05 and 2.61 [40].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although the b-value was less than 3 in numerous studies [5,19,22] of polychaetes conducted around the world, b reached 3.52 in Armandia maculata (Opheliidae), 4.27 in Bithynia tentaculata (Bithyniidae), and 2.36 in Naticidae mesogastropod species [29]. In addition, the mud crab (Scylla olivacea), found in Bangladesh's Sundarbans mangrove, has b-values of 3.05 and 2.61 [40].…”
Section: Discussionmentioning
confidence: 98%
“…For example, the study area, habitat, season, etc., play pivotal roles in determining population. Due to higher temperatures and a greater abundance of food sources, northern hemisphere species usually have reproductive seasons limited to the spring and/or summer and, most crucially, show seasonal maturation, with substantially varied growth rates throughout the life cycle [40][41][42][43][44][45][46][47]. Seasonal growing peaks, shown in temperate species, may still not appear in tropical and subtropical environments, and breeding may occur year-round [48,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mikpon et al (2020) also reported that most economically important aquatic resources, including crabs, are harvested by both industrial and artisanal fisheries in an unsustainable and uncontrollable manner. This excessive focus on the wild crab to support the stocking population can put undue pressure on the crab stock, resulting in overexploitation, reducing genetic diversity, and jeopardising this important resource (Zhang et al, 2021;Sakib et al, 2022). The Cross River crab fishery can be effectively managed through studies that reveal population dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The Cross River crab fishery can be effectively managed through studies that reveal population dynamics. Sakib et al (2022) found that recruitment pattern, growth, and mortality rate (total, fishing, and natural mortality) are the three most important factors contributing to fish population fluctuation. However, the importance of parameters such as longevity, exploitation rate, and catch probability to population dynamics cannot be overstated.…”
Section: Introductionmentioning
confidence: 99%